2018
DOI: 10.1007/s40430-017-0953-z
|View full text |Cite
|
Sign up to set email alerts
|

Machining optimization in rotary ultrasonic drilling of BK-7 through response surface methodology using desirability approach

Abstract: In the present work, optical glass BK-7 was drilled by rotary ultrasonic machine. Response surface methodology was amalgamated with desirability approach to frame the experimental matrix and seek pragmatic solutions to cope with the real machining problems. Spindle speed, ultrasonic power and feed rate were extensively scrutinized to evaluate the machining proficiency in terms of material removal rate (MRR) and surface roughness (SR). Thereafter, ANOVA check was exercised to scrutinize the adequacy of develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…A desirability function approach postulated by Harrington and later revitalized by Derringer and Suich was used to accomplish this objective [35,36]. This approach is commonly used to optimize the multiple output responses simultaneously [37][38][39][40][41]. In this approach, each of the response variable y i is normalized to a desirability value d i which lies in between 0 and 1.…”
Section: Multi-response Optimization Of Rt-musm Process With Wc Toolmentioning
confidence: 99%
“…A desirability function approach postulated by Harrington and later revitalized by Derringer and Suich was used to accomplish this objective [35,36]. This approach is commonly used to optimize the multiple output responses simultaneously [37][38][39][40][41]. In this approach, each of the response variable y i is normalized to a desirability value d i which lies in between 0 and 1.…”
Section: Multi-response Optimization Of Rt-musm Process With Wc Toolmentioning
confidence: 99%
“…The method of ultrasonic depends on the abrasion phenomenon. Blows from the grains of the harder abrasion, brittle materials are removed [4][5][6]. Abrasion phenomenon is under curb of the tool, which regularly vibrates with low amplitude (5-75 µm) and feed [1].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the low feed rate, an adequate amount of amplitude as well as high cutting speed were selected as optimal parameters which result in decreasing the tool wear and exit crack of the drilled holes as 16.891 μm and 25.375 μm, respectively. Feed rate was found to be the most significant factor affecting the MRR and surface roughness of the holes drilled in BK7 glass using RUM [ 35 ].…”
Section: Introductionmentioning
confidence: 99%